Domain based configuration and name management for distributed systems - Twidle, K.; Sloman, M. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
An overview is given of the conic configuration environment, which applies the domain concept to the structuring of configuration and name management in a distributed system. The use of access-control lists as a security mechanism is shown. Inheritance rules are specified for access permission and access rights to maintain subdomains and overlapping domain relationships. Servers are required to maintain the domain information and location information on the components in the network. A reliable name service based on an arbitrary number of servers, which permits both partitioning and replication of information, is described.< >